Systems Biology: An Engineering Perspective - Gurumoorthy, Anand V. P. (Journal of Experimental Sciences, 2013)
Systems biology is a new biological science applied to biomedical and biological scientific research. This new field of systems biology is changing the way biology has been perceived classically. This field not only needs scientists and mathematicians but also calls for engineers willing to embrace fresh challenges. This review outlines the new opportunities available in this nascent field for significant engineering-related advances. It is anticipated that engineers will be at the forefront to motivate and lead new developments in this field via theoretical systems approaches. The aim of this article is to divert the attraction of engineers towards biological science as they can revolutionize the field of biology.